Career proactivity: A bibliometric literature review and a future research agenda. Issue 1 (17th November 2022) - Jiang, Zhou; Wang, Ying; Li, Wanlu; Peng, Kelly Z.; Wu, Chia‐Huei
Abstract: Individuals often need to be proactive in order to successfully navigate their career development journeys. To what extent one is vocationally proactive has critical implications for his or her attitudes, behaviors, and other outcomes in career and work‐related settings. However, research in career proactivity has been accumulating from divergent perspectives, resulting in a substantially fragmented literature that has not been comprehensively, objectively synthesized to guide the field to move forward. To advance the domain of career proactivity, this paper synthesizes theoretical and empirical literatures using two major bibliometric analyses. We first analyze the intellectual basis of the career proactivity literature by performing document citation analysis. We then review the developmental trends of main conceptual themes in career proactivity literature using a temporal co‐word analysis. Informed by these bibliometric findings, we propose a roadmap for future research highlighting the need to clear up concepts, account for context, develop new meso‐level theories, and bridge the domains of organizational behavior and vocational development.